SENGKETA PERBATASAN INDONESIA-MALAYSIA: SEBUAH PERTARUHAN KEDAULATAN NKRI - Dewi Krisna H (Kajian Hukum, 2016)
This study aimed to analyze the measures the Government in strengthening the sovereignty of Indonesia in the border region, which includes the strengthening in the areas of national defense, science and technology, as well as strengthening in the field of foreign policy. Indonesia's national sovereignty repeatedly at stake in the face of the world when it happens to border disputes with some neighboring countries, namely Malaysia, Singapore, and the Philippines. As for the problem within the borders of sovereignty is related to a claim made by Malaysia against some of the areas that became the border area between the Republic of Indonesia and Malaysia. There are at least three cases of border disputes that make the relationship between Indonesia and Malaysia heats up, the Ambalat case, Sipadan-Ligitan, and recently is happening is Tanjung Datu. Indonesia and Malaysia border disputes does not necessarily happen. Dispute Indonesia and Malaysia on the border line in the waters of Sulawesi following a change in the ownership status of the islands of Sipadan and Ligitan, the border line on the island of Borneo (Ambalat), and the latter case that has yet to be resolved by the construction of the stake by Malaysia in Tanjung Datu (West Kalimantan). It is a trigger factor rift diplomatic relations the two countries.In this regard, there needs to the appropriate strategy with regard to strengthening the sovereignty of the Homeland border region is the duty of the Government in an effort to protect the people and maintain the territorial integrity of NKRI. Some recommendations dispute resolution sovereignty border areas studied in this paper, including: (1) Establishing institutional aspects of defense and security by providing strong security of island-outer islands, (2) Establishing institutional aspects of science and technology to conduct training on the management and conservation of resources natural resources (SDA) and the building of infrastructure and transport, as well as (3) to strengthen aspects of foreign policy with increased foreign cooperation with neighboring countries, especially with Malaysia.Keywords: Dispute, Border, Defense and Security, Science and Technology,